(untitled) (Progressive Agriculture, 2014)
The objective of the present study was to determine the overall extent of contact through mobile phone to different information sources by commercial potato growers and to explore the relationships between overall extent of contact through mobile phone and their selected characteristics. The study was carried out at Imampura union under Gazaria Upazila of Munshiganj district. Data were collected from a sample of 88 potato growers by using interview schedule during September to October 2011. Appropriate scales were used in order to measure the concerned variables. Correlation test was used to ascertain the relationships between the concerned variables. Majority (71.6 per cent) of the potato growers had very low mobile phone use while 27.3 per cent of the potato growers had low mobile phone use and only 1.1 per cent had medium use with different information sources. Contact with relatives, friends; different market agents, and cold storage manager were the most important mobile phone using contact sources. Potato growers had more contact with other agents (friends and relatives, progressive potato growers etc.) compared to the input dealer and extension agents. Their characteristics such as year of schooling, household size, farm size, annual family income, attitude towards mobile phone use, knowledge on potato production and commercialization of potato had significant positive relationships with the overall contact through mobile phone; while age, organizational exposure, cosmoliteness had no significant relationships with their extent of contact through mobile phone. DOI: http://dx.doi.org/10.3329/pa.v24i1-2.19282 Progress. Agric. 24(1&2): 239 - 149, 2013